Surface electromyography : physiology, engineering, and applications - Merletti, Roberto; Farina, Dario (Piscataway, NJ : IEEE Press, 2016)
Reflects on developments in noninvasive electromyography, and includes advances and applications in signal detection, processing and interpretation Addresses EMG imaging technology together with the issue of decomposition of surface EMG Includes advanced single and multi-channel techniques for information extraction from surface EMG signals Presents the analysis and information extraction of surface EMG at various scales, from motor units to the concept of muscle synergies.
8.6 Models of Volume Conduction and Detection Systems8.7 Models of the Surface EMG Signal; 8.8 Model Validation; 8.9 Applications of Modeling; 8.10 Conclusions; References; Chapter 9: Electromyography-Driven Modeling for Simulating Subject-Specific Movement at the Neuromusculoskeletal Level; 9.1 Introduction; 9.2 Motion Capturing and Biomechanical Modeling of the Human Body; 9.3 Musculoskeletal Modeling; 9.4 EMG-Driven Musculoskeletal Modeling and Simulation; 9.5 Experimental Results and Applications; 9.6 Conclusions; Acknowledgment; References
Includes bibliographical references and index.
Vendor-supplied metadata.
Keywords: Electromyography; Muscles -- Regeneration; Electrodes; Electronic books